Intergovernmental relations around international-regional management: an approach to the Chilean experience of governance - Ovando Santana, Cristian; Álvarez, Mariano (Estudios Internacionales, 2024)
This paper, focused on a unitary state, addresses the competencies of Chilean regions in terms of international insertion through an approach that emphasizes multiple mediations, both formal and informal. Its inductive aim is to analyze the intergovernmental links that arising from Chilean foreign policy towards some of its regions. To this end, the study will examine the coordination between the Ministry of Foreign Affairs and the Regional International Affairs Units (URAI) within the framework of RIGs analysis. The analysis is drawn from workshops, questionnaires, and direct interviews with both bodies. Among the findings, it is argued that the URAIs operate in highly diverse ways, with efforts that often go beyond the international sphere and a shifting position within the regional framework.